Mechanical and free vibration properties of skin and core designed basalt woven intertwined with flax layered polymeric laminates. (November 2020) - Ramraji, K; Rajkumar, K; Sabarinathan, P
Design of fiber-reinforced polymer damping laminates has been attracting great interest in industrial sectors for lightweight structural damping applications. The present work investigates the impact of skin, core, neutral, and alternate intertwined basalt/flax fabric on the mechanical and vibrational properties of the newly designed polymeric laminate. The designed sequence structure was fabricated using a wet hand lay-up technique with hydraulic compression. Tensile and flexural strength of intertwined multilayer basalt/flax woven composite were studied. An effect of the intertwining on the tensile and flexural strength fractured surface of the composites has been further evaluated. Free vibration technique was used for recording vibration response and the related damping frequencies of intertwining composites. A cantilever mode impact hammer was used for generating periodic signals of the designed composite systems. Damping ratios and damped natural frequencies were calculated with several plies and sequence of flax/basalt woven in the composite. The experimental results revealed that the damped natural frequencies of class II, skin basalt layer intertwined seven core flax layered composite (B2F7) was high, followed by two skin basalt layers intertwined core flax layered composite (B4F5). The addition of the flax layer enhanced the natural frequency to the higher value. It was found that the skin basalt layer with intertwined flax layered B2F7 design structure exhibits maximum damping value with acceptable mechanical properties.